Pengaruh Penerapan Cleanliness, Health, Safety, & Environmental Sustainable Pariwisata New Normal di DTW Tanah Lot, Desa Beraban, Kabupaten Tabanan - Krisdayanthi, Astrid; Rai Kristina, Ni Made (Fakultas Dharma Duta, 2021)
During the Covid-19 pandemic, maximum efforts are needed to maintain the health and safety of tourists. The Clean, Health, Safety & Environment Certification Program is the process of granting certificates to tourism businesses, other related businesses/facilities, the community environment, and tourism destinations issued by the Ministry of Tourism and Creative Economy to provide a sense of security and comfort, as well as a guarantee to tourists and the surrounding community. that the place has complied with health protocols. DTW Tanah Lot is one of 6 DTWs that have obtained the CHSE certificate. The implementation of CHSE at Tanah Lot DTW greatly affected the number of visits from the end of 2020 to the beginning of 2021 before the implementation of PPKM. Travelers during the Covid-19 pandemic are more selective in determining which DTW to visit and prefer to visit a certified DTW. In addition to obtaining a CHSE certificate, Tanah Lot DTW has implemented a Health protocol that is in accordance with the guidelines for organizing tourist attractions in order to provide a sense of security and comfort for visiting tourists.